The Relative Importance of Cell Wall and Lumen Phytoliths in Carbon Sequestration in Soil: A Hypothesis - Hodson, Martin J. (Frontiers in Earth Science, 2019)
There has been much interest in the possibility that phytoliths might sequester substantial amounts of carbon and might continue to do so in soils and sediments after the death of the plant. This may contribute to mitigating climate change. However, this idea is controversial and it is unclear how much carbon is sequestered in phytoliths. High values would suggest that sequestration on a global scale could be significant, but low values would indicate insignificant sequestration. Different methodologies in preparing phytoliths give different carbon concentrations. Little interest has been shown in determining which types of phytoliths are most important for carbon sequestration. There are two main types of phytolith in plants, the cell wall types which are formed on a carbohydrate matrix, and the cell lumen types which are not. A literature survey of transmission and scanning electron microscopy studies to determine which phytoliths are cell wall phytoliths was carried out. Cell wall silicification was common in most plant organs and throughout the plant kingdom. Macrohairs, prickle hairs, and the wall protrusion of papillae are certainly cell wall types. The primary cell walls of many epidermal cells types are often silicified. Cell wall phytoliths have considerably higher carbon concentrations than lumen types. An attempt is made to model mixtures of cell wall and lumen phytoliths, containing different carbon concentrations. Literature data on carbon and nitrogen concentrations in phytoliths was used to produce C/N ratios. These showed that cell wall phytoliths had higher C/N ratios than lumen phytoliths, and that over-extraction of phytolith mixtures removes carbon preferentially from the cell wall types and leads to low C/N ratios. The dissolution of phytoliths in soils and sediments is considered, and it is unknown whether cell wall or lumen phytoliths break down faster. However, it is clear from the literature that cell wall phytoliths persist in soils and sediments for hundreds or thousands of years. The paper is brought to a climax with two hypotheses, one to explain what happens to carbon in phytoliths as they undergo preparatory procedures in the laboratory, and the other looking at dissolution and breakdown in the soil.